Price-based interference management in dense femtocell systems - Wang, Xiaocheng; Han, Qiaoni; Guan, Xinping; Ma, Kai (International journal of communication systems, 2015)
SUMMARY Femtocell technology has been drawing considerable attention as a cost‐effective means of improving cellular coverage and capacity. However, under co‐channel deployment, femtocell system in dense environment may incur high uplink interference to existing macrocells and experiences strong inter‐cell interference at the same time. To manage the uplink interference to macrocell, as well as the inter‐cell interference, this paper proposes a price‐based uplink interference management scheme for dense femtocell systems. Specifically, on the one hand, to guarantee the macrocell users' quality of service, the macrocell base station prices the interference from femtocell users (FUEs) subject to a maximum tolerable interference power constraint. On the other hand, the inter‐cell interference is also taken into consideration. Moreover, a Stackelberg game model is adopted to jointly study the utility maximization of the macrocell base station and FUEs. Then, in order to reduce the amount of information exchange, we design a distributed power allocation algorithm for FUEs. In addition, admission control is adopted to protect the active FUEs' performance. Numerical results show that the price‐based interference management scheme is effective. Meanwhile, it is shown that the distributed power allocation combined with admission control is capable of robustly protecting the performance of all the active FUEs. Copyright © 2013 John Wiley & Sons, Ltd. In this paper, we investigate a price‐based interference management scheme for dense femtocell systems, where the MBS controls the transmission powers of FUEs by pricing their resulted interference power levels at the MBS subject to a maximum tolerable interference margin. It is formulated as a Stackelberg game to jointly maximize the revenue of the MBS and the individual utilities of FUEs. Moreover, a joint distributed power allocation and admission control algorithm that requires minimal network information exchange between the MBS and FBSs is developed.